2010
DOI: 10.3109/02713683.2010.512113
|View full text |Cite
|
Sign up to set email alerts
|

Is Nail Fold Capillaroscopy Useful in Normotensive and Primary Open Angle Glaucoma? A Pilot Study

Abstract: Results confirm the thesis that vascular factors play a significant role in the pathogenesis of the glaucoma, especially in cases where the level of intraocular pressure cannot be deemed responsible for the present damage of the optical nerve. Despite the newer, technologically more developed methods for diagnostics and monitoring glaucoma, it is often not easy to establish the right diagnosis and determine further the course of the illness, since the role the intraocular pressure (IOP) plays compared to the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
0
8
1
1
Order By: Relevance
“…Gasser and Flammer 14 have examined 30 patients with NTG, 30 patients with POAG, and 30 controls and noted markedly reduced blood velocities in NTG patients, especially after cold exposure. Bozic et al 15 have studied various morphologic features (but not hemorrhages) in NTG (n ¼ 30) versus high tension glaucoma (n ¼ 30) and found more vascular tortuosity in NTG patients. In a case-only analysis, Lee et al 16 have found significant correlation between dilated capillaries and serum matrix metalloproteinase (MMP)-9 levels as well as between avascular zones and serum MMP-9 levels in 25 NTG patients.…”
Section: Discussionmentioning
confidence: 99%
“…Gasser and Flammer 14 have examined 30 patients with NTG, 30 patients with POAG, and 30 controls and noted markedly reduced blood velocities in NTG patients, especially after cold exposure. Bozic et al 15 have studied various morphologic features (but not hemorrhages) in NTG (n ¼ 30) versus high tension glaucoma (n ¼ 30) and found more vascular tortuosity in NTG patients. In a case-only analysis, Lee et al 16 have found significant correlation between dilated capillaries and serum matrix metalloproteinase (MMP)-9 levels as well as between avascular zones and serum MMP-9 levels in 25 NTG patients.…”
Section: Discussionmentioning
confidence: 99%
“…Nailfold capillary videomicroscopy is used for diagnostic purposes in rheumatology 19 and has served a role in defining vascular changes in primary open-angle glaucoma (POAG). [20][21][22] Although nailfold capillary hemodynamics in XFS have been assessed, 16 the nailfold capillary morphology in XFS/XFG has never been studied. The nailfold capillary bed shares the same hairpin loop architecture as the iris microvasculature 23,24 and thus may serve as a useful surrogate to gain further insight into the systemic manifestations of XFS/XFG.…”
Section: Introductionmentioning
confidence: 99%
“…In the sample examined as a part of the present study, no statistically significant differences in the capillary row density were noted among the XFG, POAG, NC and XFS groups. In their study, Bozic et al [23] also conducted nailfold capillaroscopy using the same method and capillaroscopy protocol as those adopted in the present investigation. However, their sample comprised of patients with POAG and normotensive glaucoma (NTG).…”
Section: Discussionmentioning
confidence: 99%
“…Nailfold capillaroscopy can provide valuable information regarding the state of the vascular system at the capillary level, as well as the microvasculature at the junction of the fingernail and skin. Nailfold capillaroscopy is presently used for diagnostic purposes in rheumatology [20], while assisting in defining vascular changes in POAG and normal-tension glaucoma (NTG) [21,22,23].…”
Section: Introductionmentioning
confidence: 99%